1668: An Annus Horribilis for the Spanish Monarchy – The Lost European Hegemony, the International Situation, the Internal Crisis - Rafaella Pilo (Athens Journal of History, 2024)
1668 seems to be a kind of annus horribilis for the Spanish Monarchy that had been able to lead European politics during an entire century. If it possible to consider the peace of Cateau-Cambrésis of 1559 - that ended with French-Spanish conflict in Italy - such as the apical moment for Habsburg power in Europe, in some way the peace of the Pyrenees, signed in 1659 between the same protagonists, can represent the final phase of such as hegemony ruled by Madrid. Indeed, 1668 represents the most crucial point of crisis for a lot of reasons clearly connected with international order and especially with the rise of France, but also with the complicated Spanish domestic situation.